1992
DOI: 10.1039/an9921700493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the uptake of radiocaesium from soil to grass after nuclear weapons tests and the Chernobyl accident

Abstract: In order to compare the transfer factors of 137Cs deposited after the fallout from the Chernobyl accident with 137Cs from nuclear weapons testing, soil and vegetation samples have been collected from a semi-natural ecosystem in western Norway. For the 137Cs from Chernobyl, 85% is found in the upper 5 cm of soil, whereas most of the nuclear weapons test 137Cs is found between 3 and 12 cm in the soil profile. The transfer factors from soil to vegetation are calculated to be 0.41 +/- 0.07 m2 kg-1 for the nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…It has been proved in earlier studies that humus plays an increasing role in buffering cesium activity in solutions of soils rich in organic matter (Sanchez et al 1999). The data generated from the present investigation is in agreement with the findings of Selnaes and Starnd (1992). Rosen et al (1999) has reported that Cs-migration was less on mineral soils than on organic and podzolized soils.…”
Section: Discussionsupporting
confidence: 96%
“…It has been proved in earlier studies that humus plays an increasing role in buffering cesium activity in solutions of soils rich in organic matter (Sanchez et al 1999). The data generated from the present investigation is in agreement with the findings of Selnaes and Starnd (1992). Rosen et al (1999) has reported that Cs-migration was less on mineral soils than on organic and podzolized soils.…”
Section: Discussionsupporting
confidence: 96%
“…However, it can be an important source in some circumstances, for example, animals grazing tidally inundated pastures near the Sellafield reprocessing plant, can ingest over 90% of their radiocaesium intake in the form of contaminated silt particles deposited by the tide on vegetation surfaces , and roughly 60% of radiocaesium in sheep tissues has been estimated to be derived from the silt even though the A t for Cs ingested in this form is only of the order of 0.1 Singleton et al, 1992). After the Chernobyl accident, transfer coefficients (radionuclide activity concentration in animal product relative to the daily radionuclide intake) for recently deposited radiocaesium were reported to be lower than for plant-incorporated radiocaesium (Ward and Johnson, 1989;Hansen and Hove, 1991;Howard et al, 1989;Selnaes and Strand, 1992); the A t of radiocaesium cut three days after deposition from the Chernobyl accident was lower than that of Cs incorporated into vegetation by root uptake (Fig. 1).…”
Section: Values Derived From Literature Reviewmentioning
confidence: 96%
“…Humus was thought to play an increasing role in buffering 137Cs activity in solution in 0 1995 Blackwell Science Ltd. soils richer in organic matter. Thus plant uptake of 137Cs from soil has been seen to increase with increasing organic matter content (Selnaes & Strand, 1992;Cremers et al, 1990;Graham & Killion, 1962;Frissel et al, 1990). Caesium in the soil solution may be in equilibrium with an adsorbed labile pool.…”
Section: Introductionmentioning
confidence: 99%